The Eloquent Blood: The Goddess Babalon and the Construction of Femininities in Western Esotericism, by Manon Hedenborg White. - Feraro, Shai (International journal for the study of new religions, 2020)
The Eloquent Blood: The Goddess Babalon and the Construction of Femininities in Western Esotericism, by Manon Hedenborg White. 2020. Oxford University Press, 368pp., Hb £71. ISBN-13: 9780190065027.